MINIMASI BIAYA MENGGUNAKAN METODE ECONOMIC MANUFACTURING QUANTITY (EMQ) MULTI PRODUK PADA PT SEGAR MITRA NUSANTARA - Maulana Malik, Diki
PT Segar Mitra Nusantara is a manufacturing company engaged in the production, distribution, and marketing services of packaged drinking water (Air Minum Dalam Kemasan or AMDK). The company's product range includes various types of bottled water, such as 120 ml glass mineral water, 220 ml glass mineral water, 330 ml bottled mineral water, 600 ml bottled mineral water, 1500 ml bottled mineral water, and 19L gallon-sized water. The company's production system has not been running smoothly due to unstructured production planning. At times, the company produces beyond its capacity, while at other times, production is not carried out. Consequently, poor planning can lead to adverse effects on the company, including damage to product quality, high-cost burdens, and suboptimal machine utility usage.